Influence of alloying elements on the corrosion of fine art bronze in the strong corrosive environment - Ha, Bui Binh; Hai, Nguyen Hong; Khanh, Pham Mai; Tinh, Ta Dinh (Vietnam Journal of Chemistry, 2017)
The influence of Sn, Zn, and Pb on the corrosion of fine art bronze in strong corrosive environment were investigated. The value of loss mass and the potential of the specimens were determined in the artificial sea-water environment. Corrosion of specimens was compared each to other to find the effect of the elements. The corrosion products were determined with the XRD/SEM/EDS analyses. The results shown that, Sn decreases the corrosion rate of the bronze alloy in marine environment while Zn increases it. The corrosion rates and potential curves showed that the corrosion rate of the bronzes reduced with immersion time. Alloy containing 0.7% Pb; 1.6% Zn; 9.7 % Sn; 88% Cu (in %wt.) has the corrosion rate as lowest. Keywords. Corrosion, strong corrosive environments, fine art bronze, Sn, Pb, Zn.